Muslim Leadership in Luweero District 1972-2024 - Khamis, Lubega Twaha (European Journal of Applied Sciences, 2025)
This study explores the evolution of Muslim leadership in Luweero district from 1972-2024, highlighting its historical and socio-political contexts. It examines the challenges faced by Muslim leaders, their contributions to community development, and the implications of their leadership styles on inter-religious relations. Through a comprehensive analysis based on qualitative interviews and available archival data, this research reveals the complexities of Muslim leadership in a predominantly Christian region, emphasizing the role of cultural identity and community solidarity. The findings indicate that while challenges such as marginalization and political instability persist, Muslim leadership has made significant strides in promoting social cohesion and economic empowerment in the district. The paper concludes with recommendations for fostering inclusive leadership practices that bridge religious divides and enhance community development.